2005
DOI: 10.1093/annonc/mdi043
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CK-19 mRNA-positive cells in the peripheral blood of breast cancer patients with histologically and immunohistochemically negative axillary lymph nodes

Abstract: Direct hematogenous dissemination of occult tumor cells may occur in a substantial proportion of patients with early-stage breast cancer. The prognostic implication of the detection of these cells requires long follow-up periods and further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…For instance, in a study of 47 patients without overt metastasis, all the patients with DTC in PB had micrometastasis in BM, whereas 36% of patients with micrometastasis in BM had no circulating cells in PB; there was no correlation between DTC in PB or BM and micro-metastasis in SLN (Zhu et al 2005). The absence of correlation between DTC in LN and DTC in PB has also been shown by other investigators (see the recent papers of Stathopoulos et al 2005, Wülfing et al 2006.…”
Section: Prognosis and Correlationsmentioning
confidence: 60%
See 1 more Smart Citation
“…For instance, in a study of 47 patients without overt metastasis, all the patients with DTC in PB had micrometastasis in BM, whereas 36% of patients with micrometastasis in BM had no circulating cells in PB; there was no correlation between DTC in PB or BM and micro-metastasis in SLN (Zhu et al 2005). The absence of correlation between DTC in LN and DTC in PB has also been shown by other investigators (see the recent papers of Stathopoulos et al 2005, Wülfing et al 2006.…”
Section: Prognosis and Correlationsmentioning
confidence: 60%
“…Data indicating either the persistence or the disappearance of DTC after systemic treatment have been obtained (Braun et al 2000a, Smith et al 2000, Manhani et al 2001, Xenidis et al 2003, Bozionellou et al 2004, Hennessy et al 2005, Pachmann et al 2005, Pantel & Woelfle 2005, Slade et al 2005, Stathopoulos et al 2005, Drageset et al 2006, Quintela-Fandino et al 2006. Such discrepancies might reflect differences in the proliferation status of DTC or in the therapeutical agent used.…”
Section: Prognosis and Correlationsmentioning
confidence: 99%
“…To investigate further the significance of deregulated corepressor expression in breast cancer, we examined 21 matched tumor and normal breast cancer samples. To allow for epithelial enrichment in the tumor samples, the relative levels of corepressors were normalized to cytokeratin 19 mRNA, an established marker of mammary epithelial cells (39). There was considerable variation in the level of the VDR in both the ERapositive (14 of 21) and ERa-negative (7 of 21) tumors with a mean fold change of 4.9 F 2.1 and 11.8 F 7.3, respectively, compared with the matched normal, although there was significant variation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some groups have found that circulating tumor cells of inoperable breast cancer patients are associated with worse recurrence-free and overall survival (15)(16)(17). In contrast, others have reported that the presence of disseminated tumor cells is not convincingly associated with worse survival in operable breast cancer patients (8,18,19). In addition, the prognostic relevance of detection of disseminated tumor cells in the bone marrow of metastatic renal cell carcinoma patients has also been recently shown (20).…”
Section: Introductionmentioning
confidence: 99%